Target Elimination-Denatured and Unstable Proteins, Environmental Toxins, Metabolic Wastes, Immunosuppressive Factors and Chronic Inflammatory Factors of Medical System for Chronic Diseases Prevention and Health Promotion: A Narrative Review - Jiren ZHANG; Zhaojing JIANG; Wenjuan WEI; Xufeng LI; Chen SUN; Yuanyuan ZHANG; Shilin FU; Jingfen ZHENG (Tehran University of Medical Sciences, 2019)
Background: The incidence of chronic diseases, such as cardiovascular disease, diabetes, overweight, obesity, cancer and other diseases has been increasing. It is a huge challenge to public health industry about how to provide risk intervention and preventive medical services and explore advanced technology platform for effective prevention and control of chronic diseases. Methods: We collaborated domestic and international experts on preventive medicine, and analyzed pathogenesis and risk factors for the major chronic diseases. Results: We established Target Elimination--denatured and unstable proteins, environmental toxins, metabolic wastes, immunosuppressive factors and chronic inflammatory factor (TE-PEMIC) system that offer us the standard and methods to eliminate and intervene pathogenic factors of the chronic diseases. Conclusion: It provides new researches and exploring new ideas to prevent and intervene chronic diseases by applying the TE-PEMIC chronic diseases prevention medical technology system.